2017
DOI: 10.6061/clinics/2017(08)07
|View full text |Cite
|
Sign up to set email alerts
|

Selenocysteine modulates resistance to environmental stress and confers anti-aging effects in C. elegans

Abstract: OBJECTIVE:The free radical theory of aging suggests that cellular oxidative damage caused by free radicals is a leading cause of aging. In the present study, we examined the effects of a well-known anti-oxidant amino acid derivative, selenocysteine, in response to environmental stress and aging using Caenorhabditis elegans as a model system.METHOD:The response to oxidative stress induced by H2O2 or ultraviolet irradiation was compared between the untreated control and selenocysteine-treated groups. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Dietary supplementation with antioxidants including silymarin and phycoerythin can enhance locomotion rate and increase lifespan (36,37). Lifespan-extending selenocysteine can also significantly delay age-related decline of motility in C. elegans (38).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with antioxidants including silymarin and phycoerythin can enhance locomotion rate and increase lifespan (36,37). Lifespan-extending selenocysteine can also significantly delay age-related decline of motility in C. elegans (38).…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, selenium levels can extend the replicative life span of human fibroblasts when added during early-stage expansion ( 14 ). In addition, dietary supplementation of Sec, a selenium-containing cysteine, leads to lifespan extension in C. elegans ( 21 ). However, the relationship between Sec and replicative senescence in hMSCs is not known.…”
Section: Resultsmentioning
confidence: 99%
“…However, in Drosophila, selenocysteine synthesis was not essential for oxidative stress and longevity ( 20 ). Interestingly, a recent study demonstrated that dietary supplementation of Sec could modulate resistance to environmental stress, with anti-aging effects in Caenorhabditis elegans ( C. elegans ) ( 21 ). Despite these observations at the organismal level, a potential role for Sec in mammalian cells during cellular senescence has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Selenoprotein can also reverse age-related decline of molting in C. elegans ( 27 ). Our previous study has shown that dietary supplementation with selenocysteine can increase resistance to environmental stressors such as oxidative stress and ultraviolet irradiation in C. elegans ( 28 ). Selenocysteine can also extend lifespan of C. elegans without reducing its fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Selenocysteine can also extend lifespan of C. elegans without reducing its fertility. It can also delay age-related decline of its motility ( 28 ).…”
Section: Introductionmentioning
confidence: 99%